Analisis penerapan fikih muamalah dalam produk pembiayaan di bank syariah indonesia (BSI) - Rahayu, Rossa Kurnia; Shabrina, Intan; Mu’is, Ahmad (Maliki Interdisciplinary Journal, 2026)
This study explores the implementation of murabahah financing at Bank Syariah Indonesia (BSI) through the lens of fiqh muamalah and maqasid sharia, while also assessing its alignment with the latest legal and regulatory developments in Indonesia’s Islamic banking sector. Employing a qualitative descriptive–comparative approach, this research combines theoretical interpretation with an examination of contemporary regulatory frameworks. The data are drawn from primary sources such as DSN-MUI fatwas, PSAK 102, and the Financial Services Authority (OJK) regulations, as well as secondary references including academic journals and Islamic banking reports. The analysis reveals that BSI’s murabahah practices generally conform to fiqh muamalah principles, particularly regarding price transparency, clarity of the transacted object, and the determination of profit margins. However, comparative findings with Bank Muamalat and BRI Syariah indicate differing emphases in applying sharia principles, notably in ownership transfer and margin management mechanisms. From a regulatory perspective, the introduction of POJK No. 6/2023, POJK No. 22/2023, and PSAK 102 (Revised 2021) has strengthened accountability, sharia compliance, and consumer protection within the Islamic banking industry. Overall, the study concludes that murabahah financing in Indonesia is evolving from a traditional sales-based transaction toward a modern financing model that reflects maqasid sharia values and sustainability objectives.